2021
DOI: 10.14245/ns.2142412.206
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Technologies in the Treatment of Adult Spinal Deformity

Abstract: Outcomes for adult spinal deformity continue to improve as new technologies become integrated into clinical practice. Machine learning, robot-guided spinal surgery, and patientspecific rods are tools that are being used to improve preoperative planning and patient satisfaction. Machine learning can be used to predict complications, readmissions, and generate postoperative radiographs which can be shown to patients to guide discussions about surgery. Robot-guided spinal surgery is a rapidly growing field showin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 80 publications
(119 reference statements)
0
11
0
Order By: Relevance
“…One of the major issues after TES is the reconstruction of the spinal column. Solid bony fusion has been established as the most important factor to prevent mechanical failure when the 3 spinal columns are destabilized [ 15 - 17 ]. Even in the first report of TES by Dr. Tomita et al [ 1 ], a case of mechanical failure and a displaced pedicle screw were reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major issues after TES is the reconstruction of the spinal column. Solid bony fusion has been established as the most important factor to prevent mechanical failure when the 3 spinal columns are destabilized [ 15 - 17 ]. Even in the first report of TES by Dr. Tomita et al [ 1 ], a case of mechanical failure and a displaced pedicle screw were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, previous studies have suggested posterior revision surgery using multiple rods and an additional bone graft as an option [ 8 , 24 - 27 ]. A multiple-rod system has been suggested to be useful in deformity surgery, especially when 3 columns were resected to correct the deformity [ 15 - 17 , 28 - 32 ]. This suggestion is also applicable after TES [ 21 - 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…ML uses computational algorithms from repeatedly trained data to develop mathematical models built using multiple variables and large quantities of data [81]. These complex algorithms can detect more subtle patterns in data than traditional statistical methods [87]. Kim et al [88] used ML to predict surgical complications in patients who underwent elective ASD surgery and found that it improved their risk prognostication system.…”
Section: Future Directionsmentioning
confidence: 99%
“…Recently, minimally invasive surgery (MIS) for spinal fusion is widely accepted as a safe and effective surgical method. [11][12][13] The intrinsic advantages of minimal tissue disruption have been related to decreased blood loss, shortened hospital stay, and improved postoperative surgical outcomes. These advantages may be particularly applicable to surgical patients with several medical comorbidities that are affected by lumbar deformities.…”
Section: Introductionmentioning
confidence: 99%